2020
DOI: 10.1016/j.jcis.2020.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Review on heterogeneous photocatalytic disinfection of waterborne, airborne, and foodborne viruses: Can we win against pathogenic viruses?

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
112
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 443 publications
(112 citation statements)
references
References 106 publications
0
112
0
Order By: Relevance
“…Microbial pathogens, which include various bacteria and viruses, are major health concerns to humans worldwide. They occasionally cause serious infectious disease pandemics, such as those caused by the novel coronavirus (COVID-19), severe acute respiratory syndrome coronavirus (SARS), swine influenza virus (H1N1), and Middle-East respiratory syndrome coronavirus (MERS) [ 16 ]. For the sake of human health, society needs effective microbial disinfection systems with enough versatility to attack airborne, waterborne, and foodborne pathogenic species.…”
Section: Explored and Potential Applications Of Btomentioning
confidence: 99%
See 2 more Smart Citations
“…Microbial pathogens, which include various bacteria and viruses, are major health concerns to humans worldwide. They occasionally cause serious infectious disease pandemics, such as those caused by the novel coronavirus (COVID-19), severe acute respiratory syndrome coronavirus (SARS), swine influenza virus (H1N1), and Middle-East respiratory syndrome coronavirus (MERS) [ 16 ]. For the sake of human health, society needs effective microbial disinfection systems with enough versatility to attack airborne, waterborne, and foodborne pathogenic species.…”
Section: Explored and Potential Applications Of Btomentioning
confidence: 99%
“…Besides, TiO 2 could be a good option for microorganism disinfection that is low cost, requires minimal energy consumption, and is harmless and eco-friendly [ 46 , 47 ]. In the TiO 2 photocatalysis microorganism disinfection process, the ROS generated from photocatalytic processes after light irradiation plays the major roles [ 16 ]. To further boost the microbial pathogens inactivation performance of TiO 2 , we need to strengthen the producing amount of ROS species.…”
Section: Explored and Potential Applications Of Btomentioning
confidence: 99%
See 1 more Smart Citation
“…The cell infectivity assay demonstrated that the virus strains were disinfected within one minute of UV exposure [11] . Although TiO 2 holds several advantages such as non-toxic, highly economical, and chemical stability, utilization of more sustainable resources including visible/solar light for microbial disinfection is highly desirable in the future [97] . More selective viral inactivation techniques, especially towards the disinfection of SARS-CoV-2 should be further established.…”
Section: Recent Advancesmentioning
confidence: 99%
“…Moreover, the inert, non-toxic, and economic nature makes TiO 2 more favorable in the development and industrial process without the introduction of environmental issues [ 9 ]. During the ongoing COVID-19 coronavirus pandemic, TiO 2 as a potential, environment-friendly antivirus agent will gain more concerning in the practical applications [ [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%